Estudo da síntese de amostras do sistema Si2Sb2Te5 por imagem de alta energia - ESTEVAM , Jean Pierre da Silva (2016)
The purpose of this research was to demonstrate that it is possible to obtain polycrystalline samples of the Si2Sb2Te5 system, by means of High-Energy Ball Milling (HEBM). HEBM has attracted attention due to its simplicity, being briefly defined as a mechanochemical synthesis of mixtures among them powders of a very high degree of purity of different materials, which are submitted to milling in order to obtain a homogeneous alloy. The interest phase of the purpose of this study is the Si2Sb2Te5 that has applicability in the electronic device industry in data storing optic products, due to its peculiar aspects that make it one of the phase change materials most considered for the next generation of non-volatile data storing devices. In this study, it was demonstrated that HEBM can be used to synthesize Si2Sb2Te5, for after a period of 6 hours of milling of the Silicon (Si), Antimony (Sb) and Tellurium (Te) powders in the 2:2:5 stoichiometry, respectively, the powders were characterized by X Ray Diffraction, and analyzed by means of Scanning Electron Microscopy and Energy Dispersive Spectroscopy, which confirmed the development of the desired phase. The average size of the particles after milling, assessed by a specific software made for this purpose, was of approximately 0,542807µm ± 0,161021µm.